2020
DOI: 10.1007/s41783-020-00101-0
|View full text |Cite
|
Sign up to set email alerts
|

Transmittance and Survival of SARS-CoV-2 in Global Trade: The Role of Supply Chain and Packaging

Abstract: We are living in uncertain times and facing a paradigm shift in human health and sustainability. The number of SARS-CoV-2 victims is rising daily and all nations are going through dramatic effects and exploring various solutions to this imminent calamity facing the humanity. The world is confronting a public health issue that has forced it to come to a halt and evaluate the future of our modern society and our way of living. It can be stated that the sustainability of our societies inextricably depends on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Another problem related to food packaging is the possibility that SARS-CoV-2 can survive for a relatively long time in food packaging surfaces. Although there are mostly uncertainties on how long the virus could survive on different surfaces ( Hakovirta & Hakovirta, 2020 ; Malenovská, 2020 ), there are evidences that food packaging materials may carry the virus, as recently reported by China in packaging with Brazilian chicken ( Associação Brasileira de Proteína Animal, 2020 ; Kampf et al, 2020 ). Despite the contact with surfaces not being the main route of COVID-19 transmission, it also raised concerns about cross-contamination, which stimulated the culture of disposal and the indiscriminate use of non-biodegradable packaging, generating setbacks to sustainable policies already established ( Sharma et al, 2020 ; Sinclair et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another problem related to food packaging is the possibility that SARS-CoV-2 can survive for a relatively long time in food packaging surfaces. Although there are mostly uncertainties on how long the virus could survive on different surfaces ( Hakovirta & Hakovirta, 2020 ; Malenovská, 2020 ), there are evidences that food packaging materials may carry the virus, as recently reported by China in packaging with Brazilian chicken ( Associação Brasileira de Proteína Animal, 2020 ; Kampf et al, 2020 ). Despite the contact with surfaces not being the main route of COVID-19 transmission, it also raised concerns about cross-contamination, which stimulated the culture of disposal and the indiscriminate use of non-biodegradable packaging, generating setbacks to sustainable policies already established ( Sharma et al, 2020 ; Sinclair et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results of the rather scarce number of studies on the topic found in the scientific literature and here reviewed, clearly pointed out that infection risk from SARS-CoV-2 through contaminated foodstuffs and packaging is very low ( Anelich et al, 2020 ; Ceylan et al, 2020 ; Hakovirta and Hakovirta, 2020 ; Olaimat et al, 2020 ). Although foodborne transmission has not been evidenced, by contrast, some incidents with frozen foods have been reported ( Han et al, 2020 ; Liu et al, 2020 ).…”
Section: Persistence and Stability Of Sars-cov-2 In Foodsmentioning
confidence: 82%
“…Although many publications pointed out that infection risk from SARS-CoV-2 through contaminated foods and packaging is very low (Anelich et al, 2020 ; Ceylan et al, 2020 ; Hakovirta & Hakovirta, 2020 ; Olaimat et al, 2020 ), consumers and food practitioners are still worried about the food safety under the background of COVID-19 pandemic. For the purpose of managing food safety risks and the chances of food contamination, the food industry should strictly follow the Food Safety Management Systems (FSMS) based on the Hazard Analysis and Critical Control Point (HACCP) principles (Djekic et al, 2011 ; Tomasevic et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%